DETERMINAN INTENSITAS KERAWANAN PANGAN SERTA HUBUNGANNYA DENGAN FOOD COPING STRATEGIES DAN TINGKAT KECUKUPAN ENERGI DI KECAMATAN RAWAN DAN TAHAN PANGAN - Ikeu Tanziha; Hardinsyah Hardinsyah; Mewa Ariani (Food and Nutrition Society of Indonesia, 2010)
The objective of the study was to analyze the correlation among intensity of food insecurity and food coping strategy with energy intake and child nutritional status. The study design was a crosectional study. Research was conducted in Pandeglang Distric, in April - May – July 2009. A purposive sampling were applied to select 220 households. The data collected include socio economi, food coping strategy, intensity of food insequrity and, food intake. The Rank Sperman and Pearsons test were applied to analyse correlation between variable socio economic, food insecurity intensity, food coping strategy and energy intake. Logistic regression was used to analyze determinant of food insecurity intensity. Multiple regression was used to analyse determinant of energy intake. The results showed that there were significant correlatin between intensity of food insequrity with household expenditure, and food coping startegy. Determinan of food insecurity intensity were household expenditure per capita (OR=0.033) and type of food insecurity program (OR=6.664). determinan of energy intake were food insecurity intensity, household expenditure percapita and household size.